Design Codes for Historical Irkutsk - Meerovich, Mark (project baikal, 2015)
The article presents a concept of visual environment within the boundaries of the historical settlement of Irkutsk. The concept is aimed at formation of an integrated architectural-artistic appearance and ordered arrangement of outdoor advertising and information facilities.